Effectiveness of Diorama and Augmented Reality-Assisted PjBL on Natural Science Critical Thinking - Tri Indri Susanti; Joko Siswanto; Joko Sulianto (Lembaga Bale Literasi, 2026)
This study is important because science learning in elementary schools still tends to be conventional, teacher-centered, and less optimal in developing students’ critical thinking skills. The Project Based Learning model assisted by diorama media and Augmented Reality was used to create active, concrete, contextual, and interactive learning. The integration of this model and media is expected to help students understand IPAS concepts, solve problems, and draw conclusions based on observation results. This research used a quantitative approach with an experimental method involving an experimental class and a control class. The study was conducted with third-grade students at SD IT Harapan Bunda Semarang. The sample consisted of class IIIA as the experimental class with 29 students and class IIIB as the control class with 30 students. The experimental class received IPAS instruction using Project Based Learning assisted by diorama and Augmented Reality, while the control class received conventional instruction. Data were collected through observation sheets and critical thinking tests administered as pre-test and post-test. The data were analyzed using descriptive statistics, normality testing, t-test, and N-Gain analysis. The results showed that the average score of the experimental class increased from 65.2 to 92.3, while the control class increased from 54.9 to 70.8. The t-test showed a significant difference between the experimental and control classes, with a significance value of 0.000 < 0.05. The N-Gain score of the experimental class reached 0.778 in the high category, while the control class reached 0.351 in the medium category. These findings indicate that Project Based Learning assisted by diorama and Augmented Reality is effective in improving students’ critical thinking skills in IPAS learning.